Kant’s Perpetual Peace (1795) and the Russia-Ukraine/NATO Conflict - Olivier, Bert (Phronimon, 2024)
The work that I wish to concentrate on here, Perpetual Peace, is situated at least in the converging fields of (international and constitutional) law and politics. Given its date of publication (1795), Kant’s preceding works may all safely be said to have prepared his thinking for the progressive ideas expressed there, but to disclose the specific threads that connect each of these 12 preceding works with Perpetual Peace would require far more than a mere article. For this reason, I have confined myself largely to drawing such connections between the latter work and Kant’s seminal (and famous) essay, What is Enlightenment? (1784) before elaborating on Perpetual Peace and its implications for the current global situation, which will, therefore, also have to be reconstructed, unavoidably, from my own perspective. This article, therefore, addresses the question of “lasting” world peace through the lens of Kant’s essay on the conditions for “perpetual peace.” This is done by listing each of the six “Preliminary Articles” and three “Definitive Articles” stated by Kant, in turn, and comparing their respective requirements to current events in the extant world, specifically those surrounding the Russia-Ukraine/NATO conflict. It is demonstrated that, although Kant admitted that the principles he listed comprised an “ideal”, the present era marks a set of conditions further removed from lasting peace than ever before.